The argentinean pension system: prior and after Reform - Angelika Bucerius (Revista de Economía y Estadística, 2001)
The reform of the Argentine pension system is approached with the change, to a double system, attributing it to short-term problems, and assesses the effects achieved around evasion, the deficit and the limits of government management.